Modeling and Simulation of Catalyst-aided Low Temperature CO2 Desorption from Blended Monoethanolamine (MEA) – N-Methyl-diethanolamine (MDEA) Solution. (July 2017) - Decardi-Nelson, Benjamin; Akachuku, Ananda; Osei, Priscilla; Srisang, Wayuta; Pouryousefi, Fatemeh; Idem, Raphael
Abstract: A mathematical model for low temperature catalyst-aided CO2 desorption from loaded amines has been developed and validated against experimental data obtained from an integrated pilot plant utilizing blended 5 M/2 M MEA-MDEA using two industrial catalysts, namely, HZSM-5 and γ-Al2 O3 . The rigorous model considers the presence of electrolytes and both the physical and chemical contribution of the catalyst in the desorption process. The simulation results agreed well with the experimental desorber CO2 production rate data with an AAD of 7.7%. The validated model opens up a range of capabilities for further studies into the potential of the catalytic CO2 desorption process.